If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4z + 9z + -2z = 10 Combine like terms: 4z + 9z = 13z 13z + -2z = 10 Combine like terms: 13z + -2z = 11z 11z = 10 Solving 11z = 10 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Divide each side by '11'. z = 0.9090909091 Simplifying z = 0.9090909091
| 7(x-2)=(x+3) | | 4x+8=20-7x | | 2y+15=3y-1 | | -90=6(7n-1) | | 23X-2=16X+51 | | 1x(3x-10)=90 | | y=0.5x+6.18 | | 5(x-11-7)=16 | | 5x+2+7x=180 | | 5+18=35 | | x=38+x | | 4p-13p+1p=-150 | | 60=3*2y+3*4 | | 2(x-5)-6x=-22 | | X+7=x+(-2) | | -59+x= | | 3z+5=3z+5 | | 9(x+5)=3(x-3)+6x | | 3z+5+6z+4=9z+9 | | x-59= | | 8r+3s=66 | | -8x-9=-3(x+3)-5x | | (x+2y)and(2x-3y)= | | 3X-3.9=-4.1 | | (x+5)(y-6000)=600000 | | 24=6*(x-7) | | logx^2=5 | | 2x^2+34x+17=0 | | 12n+9=6 | | (x+3)(x+4)+(x+6)(x-3)= | | 19=-(5x+7) | | 4(y-7)=5-(6y-2) |